The Effect of Moringa (Moringa Oleifera) Leaf Extract on Weight Gain Among Under-Five Children At Seyegan Primary Health Center Sleman - Hasna Nabiha; Dita Kristiana; Fitnaningsih Endang Cahyawati (Jurnal Ners, 2026)
Undernutrition among children under five remains an important public health concern because inadequate nutrient intake may impair growth and development. Local food-based interventions are needed, particularly in primary health-care settings where underweight remains prevalent. Moringa oleifera is a nutrient-dense local plant that may be used as a complementary nutritional intervention. Objective this study is to determine the effect of Moringa oleifera leaf extract supplementation on body-weight gain among under-five children with underweight or severely underweight status in the catchment area of Seyegan Primary Health Center, Sleman, Yogyakarta. Methods this study is A pre-experimental one-group pretest–posttest design was used. The population comprised 70 under-five children with underweight or severely underweight status in Margomulyo, within the Seyegan Primary Health Center catchment area. Forty children aged 6–59 months were selected using purposive sampling. Participants received 2 g of Moringa oleifera leaf extract powder daily for 14 consecutive days, mixed with their usual food. Body weight was measured before the intervention and on day 14 using the same calibrated scale. Data were analyzed using the One-Sample Kolmogorov–Smirnov test followed by the Paired Samples t-test. Results this study is mean body weight increased from 10.2538 kg before the intervention to 10.7250 kg after 14 days, representing a mean increase of 0.4712 kg. The Paired Samples t-test showed a statistically significant difference between pre- and post-intervention body weight (t = −17.102, p < 0.001). Thirty-five participants (87.5%) were categorized as compliant with the intervention and five (12.5%) as non-compliant. Conclusion this study is administration of 2 g/day of Moringa oleifera leaf extract for 14 days was associated with a significant increase in body weight among the participating under-five children. Moringa may be considered a potential complementary local food-based nutritional intervention; however, the one-group design, short follow-up, and uncontrolled confounding factors limit causal interpretation